GALERI SASIRANGAN DI BANJARMASIN - Budiman, IGusti Bagus Arif; Agusniansyah, Nursyarif (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
The purpose of the Sasirangan Gallery design in Banjarmasin is to serve as an educational medium for local culture and a reminder for the local community, especially future generations, so that the Sasirangan fabric tradition is preserved. Sasirangan fabric, which has various motifs and is derived from South Kalimantan's signature knitting process, has become an important part of the industry in Banjarmasin. However, interest in this fabric varies with the times and trends, so preservation and promotion efforts are needed. The architectural problem that arises is how to design a Sasirangan Gallery that can be a modern promotional platform. The proposed solution is the use of the "Sequence" concept to harmonize the flow of space with the process of making Sasirangan fabric, making it easier for visitors to understand the process. The "problem seeking" architectural method is used to solve this problem, through the stages of problem identification, analysis, space identification, ideas, and solutions. The result of the application of this method is expected to create an effective visitor experience and support the educational goals and cultural preservation of Sasirangan fabric.